The influence of financial literacy, the use of peer to peer lending, and payment gateways on the financial performance of MSMES in Lamongan Regency - Yanuar Lazuardi; Erika Septiya Margareta (Institute of Accounting Research and Novation (IARN), 2025)
This study aims to test the effect of financial literacy, the use of peer to peer lending , and payment gateways on the financial performance of MSMEs. This study uses a quantitative method with an associative approach. The population in this study were all MSMEs in the food and beverage sector in Lamongan Regency. Samples were taken using a purposive sampling method with the criteria of MSME actors in the food and beverage sector in Lamongan Regency who were registered with the Lamongan Regency Cooperatives & Micro Enterprises Service, and MSME business actors who had utilized the fintech platform, namely payment gateways as online payments and peer to peer lending loan options so that a sample of 100 MSMEs was obtained. Data were obtained by distributing 100 questionnaires to MSME actors in Lamongan Regency directly via google form. Data analysis using SmartPLS version 3. The results of the study showed that financial literacy, the use of peer to peer lending , and payment gateways had a significant effect on the financial performance of MSMEs in Lamongan Regency.